NEEDS ASSESSMENT ON BIOLOGICAL LABORATORIUM STATE ALIYAH MADRASAH IN BANJARMASIN - Salabi, Ahmad (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2016)
This study aimed to describe the management of Biological Laboratory at MAN in Banjarmasin; and measures needs assessment conducted to make a representative Biology Laboratory at MAN in Banjarmasin. The field research (field research) is carried out with a qualitative descriptive approach, so that the depiction of the factual reality on the ground can be compared with the criteria or standards established in theory. The results showed that: (1) MAN Biological Laboratory in Banjarmasin already managed the planning, organizing, implementing, and monitoring; (2) Biological Laboratory MAN 1 and MAN 3 still managed together with the science laboratory the other because there is no special room, but the manager and the different administrations, whereas Biology Laboratory MAN 2 has been implemented in particular, because it already has the space as Service Standards minimal (SPM) SMA / MA; (3) Needs assessment has been carried out in accordance manager assessment steps, although it has not been made in writing in accordance analysis of the context of school infrastructure, so it is not maximized in the fulfillment of biology laboratory.Keywords : needs assessment, biology laboratorium, MAN